ENT 530 Social Media Portfolio / Nadia Hanafi - Hanafi, Nadia (2019)
This project are for subject Entrepeneurship which is all the student should take this course once in whole semester studies at Uitm. This course are basically teach student the ways how to invovled in business life. Every student need to take part and this course are compulsory for everyone. Besides that, every student need to create their own business in individually. Every lecture need to lecture this course from the begining until the end of step and this is also have a mark for student in final.